The Policy of the Russian Orthodox Church on International Labor Migrants: How the Public Role Collides with Preaching the Word - Mitrofanova, Anastasia (Religions, 2021)
The authors’ objective was to find out how and why the approach of the Russian Orthodox Church to sociocultural adaptation of predominantly Muslim international labor migrants has evolved from its initial stage to now. Research methodology is based on a critical analysis of various sources, on observations, and archival materials. The adaptation program of the Church was advertised as a secular project pursuing the goal of peacekeeping because of a tacit agreement on mutual non-proselytisation between the basic faith-based communities in Russia. The initiative, launched in December 2012, had to merge adaptation courses of all dioceses into a nationwide network that then was expected to become part of an all-Russian system of preparation for language and culture tests. The Church also planned to open its own network of testing centrescenters for migrants. The authors emphasize that, although some of the diocesan courses were successful, the initiative deteriorated due to many external and internal factors. One of them was that diocesan courses have proven to be unattractive for labor migrants; their curriculum was too thick and overloaded with information about Russian culture and Orthodox Christianity, while Muslim labor migrants preferred to adapt to their new environment with a mediation of their own networks. It is suggested by the authors that the main cause of the project’s non-fulfillment was an intra-church cleavage between the enthusiasts of adaptation who convinced that diocesan courses must aim at spreading the Orthodox faith to foreign workers, including Muslims, and the church officials who promoted secular curriculum and forbade preaching Christianity to labor migrants.